2021
DOI: 10.1186/s12936-021-03769-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of community-driven larval source management and house improvement on malaria transmission when added to the standard malaria control strategies in Malawi: a cluster-randomized controlled trial

Abstract: Background Current standard interventions are not universally sufficient for malaria elimination. The effects of community-based house improvement (HI) and larval source management (LSM) as supplementary interventions to the Malawi National Malaria Control Programme (NMCP) interventions were assessed in the context of an intensive community engagement programme. Methods The study was a two-by-two factorial, cluster-randomized controlled trial in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 35 publications
0
64
0
Order By: Relevance
“…Whereas previous studies often reported ‘cost per person protected ’, i.e. interventions protected (or were assumed to protect) the target population [ 14 , 15 , 33 ], this study used ‘cost per person’ as there was no statistical evidence of a protective effect of HI or LSM on primary entomological and epidemiological outcomes [ 24 ]. Thus, these annual per person costs are best interpreted as the average annual cost of implementing the interventions, as in the Majete trial study area.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas previous studies often reported ‘cost per person protected ’, i.e. interventions protected (or were assumed to protect) the target population [ 14 , 15 , 33 ], this study used ‘cost per person’ as there was no statistical evidence of a protective effect of HI or LSM on primary entomological and epidemiological outcomes [ 24 ]. Thus, these annual per person costs are best interpreted as the average annual cost of implementing the interventions, as in the Majete trial study area.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while proportions of water bodies treated with larvicide may be similar across settings, e.g. 86% in the rural Tanzania study [ 33 ] versus 84% in the MMP LSM/HI trial [ 24 ], also see Additional file 5 ), the costs of draining and filling, not reported in the Tanzania study, may underlie observed differences. Similarly for house improvement interventions, previous studies have reported closing eaves and screening windows, but varied in terms of additional modifications, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations